A new species of Epidendrum (Epidendroideae; Orchidaceae) from the Brazilian Atlantic Forest - Barberena, Felipe Fajardo V. A.; Gonzaga, Diego Rafael (Phytotaxa, 2016)
A new epiphytic species of Epidendrum from the Brazilian Atlantic Forest is described and illustrated. Epidendrum campos-portoi grows in Upper-Montane Ombrophilous Forest in the Parque Nacional do Itatiaia, southeastern Brazil. The new species differs from E. subpurum, the morphologically closest species, mainly in the thinner, cylindrical stem, not thickened, inflorescence in a raceme, and green flowers.